Assessment of diameters of karst holes in the design of the main gas pipeline, South Yakutia; E3S Web of Conferences; Vol. 98 : 16th International Symposium on Water-Rock Interaction (WRI-16) and 13th International Symposium on Applied Isotope Geochemistry (1st IAGC International Conference) - Strokova L. A. Ludmila Aleksandrovna (2019, 2019)
Title screen